Perkataan maka dan wacana sebelum abad ke-20 (Jurnal Bahasa, 2001)
The presence of so many words maka in texts written in Jawi character of the pre 20th period has been regarded as simply due to the fact the absence of punctuation marks in the respective character. There is no period and comma. There is no capital letter. It is expressed by A. Samad Ahmad (1979) and Virginia Matheson (1982) as I quote it in this article. The present discussion sees another possibility, rejecting the idea that maka is simply a substitute for some punctuation marks. There are two discourses with almost the same content, but they are different from each other in terms of context, the narrative and the non-narrative one. I only find maka in the narrative contexts, not in the non-narrative one. I then conclude there is a relationship between maka and the narrative context. One has to use maka if there is a necessity to connect an event in a particular (part of) sentence to that of the previous one - sometimes it may also have as well the causal element. As a non-narrative context does not require such a relationship, it is quite rare to find maka in a discourse with such a context. This is the phenomenon I am discussing and proving in the present discussion